Proposed Business Expansion of Yatai Tori using Constraint Management - Mohamad Toha; Adi Saptari; Anastasia Lidya Maukar (President University, 2024)
Yatai Tori management expects the business to double in size from its current condition while facing a minimal market growth of 3.7%. In the Market sector, performance needs to be perfect: tasty menu, Friendly Service, Clean and Attractive tools, Fast responses from the servants, and Clear and easy access to information on social media. In terms of the physical sector, the space of Yatai Tori is sufficient to handle 40 clients per day, which is double the existing performance of 15 customers per day. It should add one person to balance the workload of an employee. Following the Policy sector, management should implement employee compensation to motivate workers to increase performance. And management should find a good supplier to make the minimum possible food cost, increase the favourite menu stock, and decrease the favourite lees menu to control the capacity of Yatai Tori. To elevate the limitation, an investment of Rp. 370.000.000 and a total working capital of Rp. 30.000.000 is required, yielding an internal rate of return of 23.36%.